2012
DOI: 10.2174/1874402801205010013
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of mtDNA in Shed Hairs: A Retrospective Analysis of Material from Forensic Cases and a Pre-Screening Method

Abstract: Abstract:In crime scene investigations, shed hairs are one of the most frequently found types of biological evidence material. DNA analysis of hair can be of great significance in forensic investigations, and the sequencing of the hypervariable regions I (HVI) and II (HVII) of the mitochondrial genome has become a useful tool in this field. This paper describes a retrospective evaluation of the potential of sequence analysis of mitochondrial DNA. We examined evidentiary hair and reference samples obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Because of the difficulty of recovering nuclear DNA from shed hair, what is known about the DNA content of single shed hair comes primarily from studies of mitochondrial DNA. Studies have shown the mtDNA content of shed hairs to be highly variable in quantity and quality both within and between single hairs [4,13,18,29,30]. In addition to this natural variability are the additional factors routinely encountered in a forensic context: the age of the hair specimen, the environment from which it was recovered, and/or the chemical or physical insults to which the sample may have been subjected.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the difficulty of recovering nuclear DNA from shed hair, what is known about the DNA content of single shed hair comes primarily from studies of mitochondrial DNA. Studies have shown the mtDNA content of shed hairs to be highly variable in quantity and quality both within and between single hairs [4,13,18,29,30]. In addition to this natural variability are the additional factors routinely encountered in a forensic context: the age of the hair specimen, the environment from which it was recovered, and/or the chemical or physical insults to which the sample may have been subjected.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, hair shafts have become significant biological specimens in the fields of forensic toxicology and clinical chemistry as alternatives to blood and urine samples for drug abuse screening purposes ( Boumba et al, 2006 ). Although hair shafts are the most ubiquitous physical evidence ( Opel et al, 2008 ; Nilsson et al, 2012 ), DNA analysis using hair samples is difficult due to limited sample amounts and DNA stability. However, metagenomics analysis of the hair shaft microbiome may provide alternative evidence to augment other forensic results ( Tridico et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The touch DNA, fingerprint traces and the buccal swabs from the reference samples (positive controls) were extracted using 5% Chelex ® 100 in a final extract volume of 170 µL. The hair samples were first washed in 1% SDS solution (Invitrogen, Waltham, MA, USA), and the entire hairs (shaft and root part) were digested using a simple and efficient extraction protocol for hairs with or without roots [ 11 ]. Hairs were placed in a lysis buffer of 212 µL containing 1X PCR buffer (Applied Biosystem, Waltham, MA, USA), 240 µg/mL proteinase K (Qiagen, Hilden, Germany) and 33 mM dithiothreitol (DTT; Qiagen) at 56 °C for 7.5 h, followed by 96 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…In general, the studies have revealed that the exposure time in the water, the initial deposited amount of cellular material and the type of biological material directly impact the quality of the recovered DNA [ 4 , 5 , 9 , 10 ]. Shed and plucked hairs, for example, are known to contain small amounts of DNA, and it has been observed that >90% of the DNA in the root portion is degraded after 72 h in water [ 4 , 11 ]. In addition, the DNA quantity and quality may also be affected by the post-collection storage and transportation methods.…”
Section: Introductionmentioning
confidence: 99%